Cities, Sustainability, and Complex Dissipative Systems. A Perspective - Gallopín, Gilberto C. (Frontiers in Sustainable Cities, 2020)
The growing importance of cities as the main locus oh human activities and concentration is discussed, in terms of their role and influence in the earth System. Under this perspective, a vision of the cities as dissipative systems, capable of both gradual change and abrupt reorganizations (catastrophic and anastrophic) is presented, based on the theory of dissipative structures developed by the Nobel Price Ilya Prigogine. It is shown that cities fulfill the basic requirements of dissipative structures and therefore expected to exhibit a number of important dynamic properties. Secondly, the concept of a sustainable city is discussed, and, using a general systems approach, trace the plurality of conceptions of what a sustainable city means to differences in the valuation function used and the definition of the “system city” being considered. Sustainability is taken as social, environmental, and economic, not reducible to mere “green cities”. Finally, the dark aspects of current cities are discussed in association to general global trends and potential scenarios of the future, and the possibility of changing course towards truly sustainable paths is connected with their dissipative systems quality.